P-589 Natural endometrial preparation for single euploid frozen embryo transfer increases the likelihood of live birth in obese patients. (30th June 2022) - Ruiz, F; Liñán, A; Elkhatib, I; Bayram, A; Abdala, A; El-Damen, A; Shanker, U; Melado, L; Lawrenz, B; Fatemi, H
Abstract: Study question: Does a natural endometrial preparation for single euploid frozen embryo transfer increase the odds of live birth (LB) in obese patients? Summary answer: Compared to an artificial approach, a natural endometrial preparation for single euploid frozen embryo transfer improves the odds of LB in obese patients. What is known already: Several protocols to prepare the endometrium for frozen embryo transfer have been described with comparable clinical outcomes, and no individual protocol has been demonstrated to be superior. Likewise, no specific patient group has been defined that can substantially benefit from a natural endometrial preparation. Despite obesity being linked to adverse clinical outcomes, observational studies and clinical trials have traditionally included participants with normal weight when comparing protocols, resulting in obese patients being underrepresented in clinical research. Therefore, studies focusing on endometrial preparation protocols for frozen embryo transfer that include obese patients are required. Study design, size, duration: This study involved the analysis of a retrospective dataset including 975 single euploid frozen embryo transfer cycles performed at two tertiary referral centers between March 2017 and November 2019. The primary outcome was LB after natural and artificial endometrial preparation. Participants were stratified according to the World Health Organization Body mass index (BMI) classification into three groups (G): G1: Normal-weight ≤24.9 (n = 390), G2: Overweight 25 to 29.9 (n = 332), and G3: Obese ≥30 (n = 253). Participants/materials, setting, methods: Cycles included infertility patients attempting a single euploid frozen blastocyst transfer under natural (n = 324) or artificial (n = 651) endometrial preparation. PGT-A was performed after trophectoderm biopsy using Next-Generation Sequencing. Spontaneous LH rise confirmed ovulation for natural endometrial preparation, and embryo transfer occurred five days after initial progesterone elevation. Hormones were measured from blood samples. For artificial preparation, embryo transfer was performed after oral estradiol and 120-hour vaginal progesterone exposure. All participants received luteal phase support. Main results and the role of chance: Within each BMI group, no statistically significant differences in age were observed in patients between a natural and artificial endometrial preparation: G1 (33.5±5.1 vs. 32.7±5.2 years; p = 0.13), G2 (34.5±4.9 vs. 33.9±5.8 years; p = 0.39), and G3 (35.6±4.9 vs. 34.3±5.6 years; p = 0.1). Similarly, no statistically significant differences were observed regarding implantation rates: G1 (60% vs 57.1%; p = 0.57), G2 (54.8% vs 55.7%; p = 0.88), and G3 (64.3% vs 51.4%; p = 0.07). LB rates remained constant across all BMI groups when a natural preparation was conducted: G1 [56.66% (n = 85/150)], G2 [49.03% (n = 51/104)], and G3 [58.57% (n = 41/70)]. We observed a decrease in LB rates in G3 when an artificial endometrial preparation was performed: G1 [47.5% (n = 114/240)], G2 [44.73% (n = 102/228)], and G3 [34.42% (n = 63/183)]. The positive impact of a natural preparation on LB rates was more significant in G3, showing a 24% difference of effect between the natural and artificial endometrial preparations. Univariate logistic regression analysis showed a statistically significant difference in the primary outcome (LB) when a natural endometrial preparation was conducted in G3 (OR 2.69, 95% CI 1.53-4.74; p = 0.001), with no differences found in G1 (OR 1.45, 95% CI 0.96-2.18; p = 0.08) and G2 (OR 1.19, 95% CI 0.75-1.89; p = 0.73). Limitations, reasons for caution: This study could be subject to bias due to its retrospective nature. Sperm quality was not considered for the present study. Wider implications of the findings: Obese women appear to be the patient group that can obtain benefit from a natural endometrial preparation for frozen embryo transfer by increasing the odds of LB. Future prospective studies should confirm this hypothesis. A natural approach might be unfeasible in a subgroup of obese patients due to anovulatory cycles. Trial registration number: not applicable